Elderly Community Education System - Nurhaliza, Laila; Ritonga, Asnil Aidah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the education system and the implementation of the education system like what is in the Faeyza Ashabul Jannah institution (which is located at Limau Mungkur Street, Bangun Rejo Village, Tanjung Morawa District.) This research uses a qualitative method with a phenomenological approach. The data used in this study is the education system of the elderly. The primary data source was obtained from the Head of the Feyza Ashabul Jannah Foundation, while the secondary data source came from Ustazah and the elderly at the Faeyza Ashabul Jannah Institute. Data collection techniques using observation, interviews, and documentation. At the same time, data analysis is in the form of data reduction, data presentation, verification, or conclusion. The results of the study show that the education system for the elderly community in the Faeyza Ashabul Jannah institution is already running well in accordance with the composition of the components arranged synergistically, which work together with each other and achieve good learning and implementation forms that work well The education system for the elderly community is where the elderly experience changes for the better while participating in learning at the institution. From the data, it can be seen that the education system can run well if the education system is interconnected in a coherent manner and learning can not only be attended by children or adolescents, but the elderly also have the right to education.